Pengaruh Bauran Pemasaran Syariah dan Label Halal terhadap Keputusan Pembelian - Rika Paujiah; Ahmad Mulyadi Kosim; Syarifah Gustiawati (Prodi Perbankan Syariah FAI UMT, 2020)
This study was conducted to examine the effect of the sharia marketing mix variables and halal label on purchase decisions at d'BestO city of Bogor. This study uses a quantitative method. The sample was 86 respondents who are consumers of products d'BestO in Bogor. Analysis of the data used in this research is multiple regression analysis. The results of this study show that: sharia marketing mix significantly influence the purchase decision is evidenced bythat the value of the variable t on sharia marketing mix is 4.090 with a significance level of 0.000. Because the value of t is greater than t table is 4.090 > 1.988 and 0.000 significance value <0.05. And halal label significantly influence the purchase decision is evidenced by the value of the variable t on halal label is 3.739 with a significance level of 0.000. Because the value of t is greater than t table is 3.739> 1.988 and 0.000 significance value <0.05. sharia marketing mix and halal label jointly significant effect on purchase decisions this is evidenced by the significant value of the smaller F-test of 0.05 is equal to 0.000 (0.000 <0,05) so that it can be concluded that the sharia marketing mix and halal label significant influence on purchase decisions.